Transmission of Islamic reform (Islah) from Egypt to Malaysia: A study of Hasan al-Banna's legacy - Mamat, Ismail (Zes Rokman Resources, 2016)
One of the most well known personalities in Muslim society of the twentieth century was Hasa al-Banna (1906-1949). He was the founder of Jama'at al-Ikhwan al-Muslimin, (the Muslim Brotherhood), one of the influential Muslim organizations in Egypt. His ideas made a great impact on the Islamic movements in Malaysia particularly Parti Islam Se-Malaysia (the Islamic Party of Malaysia) (PAS) and Angkatan Belia Islam Malaysia (the Muslim Youth Movement of Malaysia) (ABIM). Islamic movements actually call for a total reform (islah) in the life of the individual, family, society and social, economic, political, legal, educational and cultural systems. They call for a holistic understanding of Islam which is not reduced to intellectual, economic, or social activities of people. Results show that Hasan al-Banna was one of the most important figures who were responsible for shaping those Islamic movements in Malaysia.